2014
DOI: 10.4049/jimmunol.1303397
|View full text |Cite
|
Sign up to set email alerts
|

CD1dhiCD5+ B Cells Expanded by GM-CSF In Vivo Suppress Experimental Autoimmune Myasthenia Gravis

Abstract: IL-10-competent subset within CD1dhiCD5+ B cells, also known as B10 cells, has been shown to regulate autoimmune diseases. Whether B10 cells can prevent or suppress the development of experimental autoimmune myasthenia gravis (EAMG) has not been studied. In this study, we investigated whether low dose granulocyte macrophage-colony stimulating factor (GM-CSF), which suppresses EAMG, can expand B10 cells in vivo, and whether adoptive transfer of CD1dhiCD5+ B cells would prevent or suppress EAMG. We found that tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 75 publications
2
36
0
Order By: Relevance
“…IL-10 derived from CD1dhighCD5+ B cells was also proven to regulate experimental autoimmune myasthenia gravis. Adoptive transfer of IL-10 competent CD1highCD5+ B cells led to higher frequency of Treg and B10 cells, and low levels of proinflammatory cytokines and autoantibody production [19]. In addition to the above discussed in vitro and animal model studies, many researchers have shown that Breg cells including their ability to produce IL10 were altered in many immune/autoimmune-mediated diseases such as RA, psoriasis, and systemic sclerosis.…”
Section: Cd19+cd38highil-10highmentioning
confidence: 97%
“…IL-10 derived from CD1dhighCD5+ B cells was also proven to regulate experimental autoimmune myasthenia gravis. Adoptive transfer of IL-10 competent CD1highCD5+ B cells led to higher frequency of Treg and B10 cells, and low levels of proinflammatory cytokines and autoantibody production [19]. In addition to the above discussed in vitro and animal model studies, many researchers have shown that Breg cells including their ability to produce IL10 were altered in many immune/autoimmune-mediated diseases such as RA, psoriasis, and systemic sclerosis.…”
Section: Cd19+cd38highil-10highmentioning
confidence: 97%
“…The implications of these data are not clear; it is possible that GM-CSF can modulate immune responses by regulating autoantibody production. In a recent study it was found that GM-CSF can expand IL-10 producing subset of CD1d high CD5 + B-cells (also called B10 cells) (146). A fusion protein comprising of GM-CSF and IL-15 has previously been shown to induce B10 cells in vitro (147).…”
Section: Introductionmentioning
confidence: 99%
“…In an EAE model, the adoptive transfer of B10 cells normalized the disease, but the transfer of IL-10 −/− B10 or other B-cell subsets did not. 80 Unsurprisingly, the adoptive transfer of B10 cells inhibited the disease even after disease onset. 80 Unsurprisingly, the adoptive transfer of B10 cells inhibited the disease even after disease onset.…”
Section: Cd19 + Cd1d Hi Cd5 + (B10) Bregsmentioning
confidence: 99%